Regulation and Ethics of Facial Recognition Systems: An Analysis of Cases in the Court of Appeal in the State of São Paulo - Oliveira, Cristina Godoy B. de; Albuquerque, Otávio de Paula; Belotti, Emily Liene; Lopes, Isabella Ferreira; Silva, Rodrigo Brandão de A.; Arbix, Glauco (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
Context: The use of Artificial Intelligence (AI) in various sectors of the economy is already a reality in Brazil. Consequently, since 2019, the number of cases in the Judiciary involving AI has increased. Cases involving facial recognition systems (FRS) for contracting bank credit are increasing annually, so it is necessary to analyze how the Judiciary handles the issues. Problem: Why is the São Paulo Court of Appeal ruling in favor of banks in all cases involving taking out credit through facial recognition technology? Methodology and Methods: Data were collected and processed using automated computer programs. The qualitative analysis used the analytical, comparative and monographic methods. Results: The Court of Appeal of São Paulo considers it difficult to deceive an AI system, therefore, the burden of proof is on the author, even if there is a consumer relationship. That is, the decisions are contrary to the general rule of the Code of Consumer Protection in Brazil, which consists of reversing the burden of proof in consumer relations when one of the parties is underprivileged. Contributions and Solutions: The research points to the path of jurisprudence in cases involving the contracting of credit through FRS, and the Judiciary is deciding against the bank’s customers, dispensing with the production of evidence by the banking sector. Therefore, it is necessary to alert the National Council of Justice and the Central Bank regarding this situation so that it is disciplined adequately since the FRS is fallible and does not guarantee the absence of fraud.